Seasonal drought classification and its characteristics in the red soil region of southern China - Yong Zhong; Lei Gao; Xinhua Peng; Asim Biswas; Wei Hu; Yaji Wang (Journal of Hydrology: Regional Studies)
Study region: The red soil region of southern China Study focus: The red soil region of southern China faces serious seasonal drought, which poses a great threat to the sustainable development of local agriculture. Yet the characterization of drought types remains unexplored due to lacking systematic classification methods. The present study addressed this knowledge gap by analyzing daily meteorological data of 444 stations from 1961 to 2019 using the Standardized Precipitation Evapotranspiration Index (SPEI). A total of 15,854 drought events were classified into three distinct types (I, II, and III) employing run theory and k-means clustering. The spatiotemporal patterns of three types’ events were further elucidated. New hydrological insights for the region: Trend analysis revealed a pronounced “warming and drying” trend, with temperature rising by 0.02°C and relative humidity declining by 0.05 % per year. Temporal analysis identified three distinct stages: dry (1961–1979), wet (1980–1999), and dry-wet alternation (2000–2019). Seasonal drought in this region has intensified since the 1990s, characterized by increased frequency, duration, severity, and intensity of the drought events. Identified three drought event types exhibited annual frequencies of 0.39, 0.17, and 0.04 time, respectively. Mild and moderate drought (Type I and II) dominated across the region, while severe drought (Type III) concentrated in northern and southeastern coastal areas. These findings offer valuable insights for drought risk management strategies in the red soil region.